Adorned by Power: The Individualized Experience of the Mojo Bag - Clausnitzer, Danielle (Religions, 2017)
In America, no religion better exemplifies the power of the individual than Hoodoo. Within these peripheral communities in the South, enslaved persons created spaces in which individual practitioners could choose which rituals, objects, and beliefs they prioritized for their own salvation. Out of this tradition of selection came the development of adornments like Mojo Bags, an amalgamation of objects, both natural and manufactured, that connect the individual directly with the sacred. When adorned with these Mojo Bags, primarily under clothes to assure contact with the skin, practitioners are provided with the power they have previously been denied. I will argue in my paper, therefore, that this method of adornment provides the locus of power needed to address the psychological and physical bondage practitioners faced during the period of enslavement, highlighted by the case of Frederick Douglass' use of a root that led to his success in fighting with Mr. Covey.